Intraocular pressure in retinal vein occlusion. Issue 1 (January 1984) - Frucht, J; Shapiro, A; Merin, S
Abstract : The intraocular pressure of 59 patients with retinal vein occlusion was studied. Central retinal vein occlusion (CVO) was diagnosed in 24 patients and branch retinal vein occlusion (BVO) was diagnosed in the rest. The intraocular pressure of a sex and age matched group of controls was also studied for comparison. The intraocular pressure in the CVO group were significantly different from those of the matched controls (p less than 0.001). A statistically significant difference of a lesser degree (p less than 0.05) was also found in a comparison of the intraocular pressures of the BVO group with those of their sex and age matched group of controls. These findings may indicate the possible role of increased intraocular pressure in the pathogenesis of CVO and BVO.